Genomisk selektion inom köttraser - Blomdahl, Stina (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2015)
Genomic selection (GS) is used for selection of breeding animals of dairy cattle. GS is though not as extensively used within the beef industry. One reason for that is the low accuracy (rTI) of the breeding value that is of great importance for the final genetic gain. Causes to the low accuracy are high effective population size, a small reference population and a genetically differentiated population. There is however a market for genomic selection with High Density (HD) tests for beef cattle. It is foremost offered to Black Angus where a HD test of 50 000 markers are used for production traits. GS for beef cattle could be utilised for traits that are expensive or difficult to measure, for example feed efficiency, marbling and tenderness. The big advantage with a well-functioning GS is that it reduces the generation interval and that enhances the final genetic gain.